2018
DOI: 10.5937/ffr1802203d
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterisation of Bacillus subtilis strain use as a dietary probiotic bio-additive in weaning piglet

Abstract: The aim of the study was to characterize the Bacillus subtilis ATCC 6051a strain, in order to establish its probiotic utility in piglet nutrition. The strain was assayed morphologically, culturally, biochemically, for hemolytic activity and enzymatically (amylase and protease). The identification and analysis of the biochemical characteristics was performed by catalase assay, API 50 CHB Biomerieux strips, apiweb API 50 CHB V 4.0 soft (B. subtilis very good identification, 99.4% ID) and ABIS online. The hemolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The strains studied in the present study were found to be non‐haemolytic. Non‐haemolytic strains of B. subtilis and B. licheniformis with probiotic potential have also been reported (Dumitru et al., 2018; Ghosh et al., 2020; Niu et al., 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The strains studied in the present study were found to be non‐haemolytic. Non‐haemolytic strains of B. subtilis and B. licheniformis with probiotic potential have also been reported (Dumitru et al., 2018; Ghosh et al., 2020; Niu et al., 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The selection criteria of BS strain was based on the probiotic properties including growth rate, identification, and characterization of capacity to ferment carbohydrate substrates (API 50 CHB), amylase and protease production, survivability in low pH, bile salts, the growth rate of spores, hemolysis production, and susceptibility to antibiotics were assessed in vitro (data not shown). The bacterial strain was grown in a nutrient medium (g/L: tryptone 10; meat extract 5; sodium chloride 5; pH medium 7.2 ± 2 before autoclaving) and incubated in a shaker-incubator (200 rpm) at 37°C for 24 h in aerobic conditions as reported previously by Dumitru et al. (2018 , 2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Coliforms were cultured on MacConkey agar (Oxoid CM0007) incubated aerobically at 37°C for 24 h as red, specifically colonies. E. coli biotype β-hemolytic was analyzed, as reported by Dumitru et al. (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Based on phenotypical identification, some characteristics from some identified strains (IBNA 29,33,41,48,50,51,56,57,61) are reported in other studies [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…Blood agar plates [Trypticase soy agar (TSA, Sanimed) containing 5% (w/v) sheep blood] were used to test hemolysis activity. Interpretation was followed after incubation at 37 • C, for 24 h [29].…”
Section: Hemolysis Testmentioning
confidence: 99%